2021
DOI: 10.1111/acps.13272
|View full text |Cite
|
Sign up to set email alerts
|

Shortening the Edinburgh postnatal depression scale using optimal test assembly methods: Development of the EPDS‐Dep‐5

Abstract: This study used a large database to develop a reliable and valid shortened form of the Edinburgh Postnatal Depression Scale (EPDS), a self-report questionnaire used for depression screening in pregnancy and postpartum, based on objective criteria. Methods: Item responses from the 10-item EPDS were obtained from 5157 participants (765 major depression cases) from 22 primary screening accuracy studies that compared the EPDS to the Structured Clinical Interview for DSM (SCID). Unidimensionality of the EPDS latent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…When asked if their current health was ‘Poor’, ‘Fair’, ‘Good’, ‘Very good’, or ‘Excellent’, 77% (17/22) of women in usual care and 71% (24/34) of women in Group Care rated their health as ‘Very Good’ or ‘Excellent’. One of the ten items in the EPDS was accidentally omitted ( I have been so unhappy that I have had difficulty sleeping ), so we used the validated 5-question version – EPDS-Dep-5 [ 23 ] to report on here. The EPDS-Dep-5 score is calculated using five questions from the original EPDS—‘ I have been able to laugh and see the funny side of things ’, ‘ I have looked forward with enjoyment to things ’, ‘ I have felt sad or miserable ’, ‘ I have been so unhappy that I have been crying ’, and ‘ The thought of harming myself has occurred to me ’ (Cronbach’s alpha 0.82 compared to 0.88 for the full EPDS).…”
Section: Resultsmentioning
confidence: 99%
“…When asked if their current health was ‘Poor’, ‘Fair’, ‘Good’, ‘Very good’, or ‘Excellent’, 77% (17/22) of women in usual care and 71% (24/34) of women in Group Care rated their health as ‘Very Good’ or ‘Excellent’. One of the ten items in the EPDS was accidentally omitted ( I have been so unhappy that I have had difficulty sleeping ), so we used the validated 5-question version – EPDS-Dep-5 [ 23 ] to report on here. The EPDS-Dep-5 score is calculated using five questions from the original EPDS—‘ I have been able to laugh and see the funny side of things ’, ‘ I have looked forward with enjoyment to things ’, ‘ I have felt sad or miserable ’, ‘ I have been so unhappy that I have been crying ’, and ‘ The thought of harming myself has occurred to me ’ (Cronbach’s alpha 0.82 compared to 0.88 for the full EPDS).…”
Section: Resultsmentioning
confidence: 99%
“…From this model, for each set of HADS-D and HADS-T paired cutoffs, we estimated the difference in sensitivity and specificity between the two tests and associated CIs. These CIs from the bootstrap approach and individual-level analysis allowed us to test whether the sensitivity and specificity of the HADS-T is equivalent to that of the HADS-D based on a prespecified equivalence margin of δ = 0.05 (Walker & Nowacki, 2011), as we have done in previous studies (Harel et al, 2021; Ishihara et al, 2019; Wu, Levis, Riehm, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This forms a series of candidate sets to be chosen from. In the third step, the smallest candidate set from step 2 that satisfies the pre‐specified criteria is selected as the optimal short form (Harel et al, 2021). Thus, the OTA is objective, with different researchers using the same set of pre‐specified criteria will obtain the same optimal short form (Harel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This avoids subjectivity in conventional item selection approaches, which may lead researchers to arrive at different short forms even using the same approach. Despite OTA being relatively new, several studies have demonstrated the robustness of using objective and predetermined criteria for item selection (Harel et al, 2019; Harel et al, 2021; Li, Fong, et al, 2020; Xiao et al, 2022). However, there has been no application of OTA in the field of nursing research.…”
Section: Introductionmentioning
confidence: 99%